Strategi Pengelolaan Materi Musikal dan Teknis Paduan Suara; Studi Kasus Pengalaman Aktivitas Pentas, Lomba, dan Penjurian - A. Gathut Bintarto T. (PROMUSIKA, 2015)
This research tried to figure out the complexity of challenges faced by the choir’s conductor or the vocal coacher especially tocomprehend deeply in the certain period the matters that can be observed to gain the optimum results that can be measuredsignificantly by the choir’s member. The early musical strategic found in the beginning of this research trying to capture theactivities of the vocal coacher based on the experiences found by the researcher during the preparation period to make thechoir’s performances or as in the position as a choir’s judge in the middle of the contest. The participated observationconducting in this research shown the datas of similar process and the final expectation between the short (1 week to 2months), middle (2,5‐4 months) and long period (more than 5 months) of the preparations. The supporting data collected inthis research shown that the imaginative abilities dan the experiences of the vocal coacher in coping with the differentsituations of the performances and the contests brought significant effects for conducting the song’s material, working withvarious rhythmical patterns, interpreting the music and for sharing the musical ideas as they processed in one or multipleevents at one time.